2019
DOI: 10.1007/s10585-019-09975-0
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological growth patterns of colorectal liver metastasis exhibit little heterogeneity and can be determined with a high diagnostic accuracy

Abstract: Colorectal liver metastases (CRLM) exhibit distinct histopathological growth patterns (HGPs) that are indicative of prognosis following surgical treatment. This study aims to assess the reliability and replicability of this histological biomarker. Within and between metastasis HGP concordance was analysed in patients who underwent surgery for CRLM. An independent cohort was used for external validation. Within metastasis concordance was assessed in CRLM with ≥ 2 tissue blocks. Similarly, concordance amongst mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 34 publications
(35 reference statements)
2
33
0
Order By: Relevance
“…This is likely of little relevance though, as interobserver reliability for HGP assessment, even for trained observers with limited histopathological experience, was found to be excellent. 48 Furthermore, within-and between-metastasis concordance of HGPs is especially high in chemo-naive patients. 48 Third, the semiquantitative IHC assessment in cohort A only incorporated grading of antibody expression and not antibody intensity compared to positive control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely of little relevance though, as interobserver reliability for HGP assessment, even for trained observers with limited histopathological experience, was found to be excellent. 48 Furthermore, within-and between-metastasis concordance of HGPs is especially high in chemo-naive patients. 48 Third, the semiquantitative IHC assessment in cohort A only incorporated grading of antibody expression and not antibody intensity compared to positive control.…”
Section: Discussionmentioning
confidence: 99%
“…48 Furthermore, within-and between-metastasis concordance of HGPs is especially high in chemo-naive patients. 48 Third, the semiquantitative IHC assessment in cohort A only incorporated grading of antibody expression and not antibody intensity compared to positive control. Previous studies have incorporated methods for scoring both antibody expression and antibody intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Average HGP percentages were calculated per metastasis and per patient (in case of multiple CRLM). This method has been validated previously, demonstrating a 95% within CRLM concordance (in case of multiple H&E slides) and a 90% between metastases concordance (in case of multiple CRLM in one patient) [14]. Patients were classified in two groups: dHGP if all available slides showed a 100% desmoplastic interface and non-dHGP if a replacement or pushing type HGP was found on one or more slides [10].…”
Section: Hgp Characterizationmentioning
confidence: 99%
“…vessel co-option) instead of angiogenesis [11,12]. Non-dHGP has been associated with a worse prognosis for patients undergoing resection of CRLM in multiple studies [10,13,14]. A large cohort study suggested that this effect was predominantly found in patients that were not pretreated with chemotherapy prior to CRLM resection [10] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…There is a pressing need for clinical oncologists to include these developments in the standardized form of assessment and subsequent documentation of metastases. In this issue, Höppener et al [2] present attempts to achieve such standards for the pathological examination of metastatic lesions. Their effort to describe and classify heterogeneity within colorectal metastases should trigger further discussion and evaluation of these proposed standardizations.…”
mentioning
confidence: 99%